Polyester resin particles and their uses
By specifying the particle diameter, enthalpy, and angle of repose, along with the use of aliphatic or aliphatic-aromatic polyester resins, the polyester resin particles achieve enhanced slip properties and a soft feel, addressing the shortcomings of existing particles in cosmetics and coatings.
Patent Information
- Application Number
- JP2023169272
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-03
- Filing Date
- 2023-09-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-09-29
AI Technical Summary
Existing polyester resin particles do not satisfy the requirements for a soft feel and slip properties, which are essential for applications in cosmetics and coatings.
The development of polyester resin particles with specific properties, including a volume-based cumulative 50% particle diameter (D50) of 1 to 100 μm, an enthalpy of fusion of 20 to 140 J/g, and an angle of repose of 20 to 65 degrees, along with the inclusion of aliphatic or aliphatic-aromatic polyester resins, enhances slip properties and soft feel.
The resulting polyester resin particles exhibit excellent slip properties and a soft feel, making them suitable for use in cosmetics and coatings, providing a pleasant application experience.
Smart Images

Figure 0007617217000001
Abstract
Description
[Technical field]
[0001] The present invention relates to polyester resin particles and uses thereof. [Background technology]
[0002] Particles are widely used in cosmetics, paints, optical applications, resins, building materials, etc. Functions required for particles include light diffusion, concealment, coatability, and touch imparting, and properties required for particles include refractive index, dispersibility, slipperiness, flexibility, etc. For example, in cosmetics and paints, particles with a soft touch are preferred in terms of touch imparting, etc. In recent years, with increasing interest in the environment, particles with low environmental impact are in demand, and biodegradable particles in particular have attracted attention. Patent Document 1 describes a method for producing polylactic acid-based resin microparticles made of polylactic acid derived from non-petroleum raw materials as particles that reduce environmental impact, and the polylactic acid-based resin microparticles. Patent Document 2 describes porous resin microparticles made of biodegradable polyester thermoplastic resin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2012 / 105140 [Patent Document 2] International Publication No. 2017 / 056908 Summary of the Invention [Problem to be solved by the invention]
[0004] However, these particles were not satisfactory in terms of feel. Therefore, an object of the present invention is to provide polyester resin particles having excellent slipperiness and a soft feel. [Means for solving the problem]
[0005] Means for Solving the Problem The present inventors have conducted intensive research to achieve the above-mentioned object, and as a result have discovered that polyester-based resin particles exhibiting specific properties can provide polyester-based resin particles having excellent slip properties and a soft feel, thereby arriving at the present invention. That is, the polyester resin particles of the present invention contain a polyester resin, have a volume-based cumulative 50% particle size (D50) of 1 to 100 μm, a fusion enthalpy of 20 to 140 J / g, and an angle of repose of 20 to 65 degrees.
[0006] The polyester resin particles of the present invention preferably satisfy at least one of the following requirements 1) to 3). 1) The maximum melting peak temperature is 50 to 250°C. 2) The oleic acid absorption is 30 to 150 mL / 100 g. 3) The polyester resin includes at least one selected from an aliphatic polyester resin and an aliphatic-aromatic polyester resin.
[0007] The cosmetic of the present invention contains the above-mentioned polyester-based resin particles. The coating composition of the present invention contains the above-mentioned polyester resin particles. Effect of the Invention
[0008] The polyester resin particles of the present invention have excellent slip properties and a soft feel to the touch. Since the cosmetic of the present invention contains the polyester-based resin particles, it has excellent slipperiness and a soft feel to the touch. The coating composition of the present invention contains the polyester resin particles, and therefore has excellent slip properties and a soft feel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The polyester-based resin particles of the present invention (hereinafter, sometimes simply referred to as resin particles) contain a polyester-based resin, have a volume-based cumulative 50% particle size (D50) of 1 to 100 μm, a fusion enthalpy of 20 to 140 J / g, and an angle of repose of 20 to 65 degrees, and have excellent slip properties and a soft feel. The polyester resin particles of the present invention will be described below.
[0010] [Polyester resin particles] The resin particles of the present invention have a volume-based cumulative 50% particle size (D50) of 1 to 100 μm. If the particle size (D50) is less than 1 μm, the smoothness is poor, and if it exceeds 100 μm, the surface feels rough and the softness is poor. The lower limit of the particle size (D50) is preferably 1.5 μm, more preferably 2.0 μm, and even more preferably 2.5 μm, and the upper limit of the particle size (D50) is preferably 50 μm, more preferably 40 μm, even more preferably 30 μm, and particularly preferably 20 μm. Furthermore, for example, 1 to 50 μm is preferable, more preferably 1.5 to 30 μm, and particularly preferably 2 to 20 μm.
[0011] The resin particles of the present invention are not particularly limited, but the value (D90 / D50) obtained by dividing the cumulative 90% particle diameter (D90) based on volume by the above-mentioned particle diameter (D50) is preferably 1.0 to 3.5. If the value is 3.5 or less, roughness due to unevenness when the resin particles are applied tends to be suppressed, and the soft touch tends to be improved. The lower limit of the value is more preferably 1.1, even more preferably 1.3, and particularly preferably 1.5, and the upper limit of the value is preferably 3.0, more preferably 2.8, even more preferably 2.5, and particularly preferably 2.2. Furthermore, for example, 1.1 to 3.0 is more preferable, 1.3 to 2.8 is even more preferable, and 1.3 to 2.5 is particularly preferable.
[0012] The resin particles of the present invention are not particularly limited, but the value (D10 / D50) obtained by dividing the cumulative 10% particle diameter (D10) based on volume by the above-mentioned particle diameter (D50) is preferably 0.1 to 1.0. When the value is 0.1 or more, the smoothness and soft touch tend to be improved. The lower limit of the value is more preferably 0.2, even more preferably 0.25, and particularly preferably 0.3, and the upper limit of the value is more preferably 0.9, even more preferably 0.8, and particularly preferably 0.7. Furthermore, for example, 0.1 to 0.9 is more preferable, 0.2 to 0.8 is even more preferable, and 0.3 to 0.7 is particularly preferable. The particle diameter (D50), particle diameter (D90), and particle diameter (D10) of the resin particles are those according to the method described in the Examples.
[0013] The melting enthalpy of the resin particles of the present invention is 20 to 140 J / g. When the melting enthalpy is within the above range, the polymer has an excellent balance between the crystallinity and the amorphous portion, the resin particles have an appropriate hardness, and are excellent in slipperiness when applied. The lower limit of the melting enthalpy is preferably 25 J / g, more preferably 30 J / g, even more preferably 33 J / g, and particularly preferably 35 J / g, and the upper limit of the melting enthalpy is preferably 130 J / g, more preferably 125 J / g, even more preferably 120 J / g, and particularly preferably 115 J / g. Furthermore, for example, 30 to 130 J / g is preferable, 33 to 120 J / g is more preferable, and 35 to 115 J / g is particularly preferable. The melting enthalpy of the resin particles is measured by the method described in the Examples.
[0014] The maximum melting peak temperature of the resin particles of the present invention is not particularly limited, but is preferably 50 to 250°C. When the melting peak temperature is within the above range, the soft touch tends to be improved. The lower limit of the melting peak temperature is preferably 55°C, more preferably 60°C, even more preferably 65°C, and particularly preferably 70°C, and the upper limit of the melting peak temperature is preferably 200°C, more preferably 190°C, even more preferably 180°C, and particularly preferably 165°C. Furthermore, for example, 60 to 200°C is more preferable, and 60 to 180°C is even more preferable. The maximum melting peak temperature of the resin particles is measured by the method described in the Examples. The resin particles of the present invention may have one or more melting peaks. Furthermore, the melting peaks of the resin particles of the present invention are not particularly limited, but it is preferable that all of the melting peaks are in the range of 50 to 250° C. in terms of achieving the effects of the present invention.
[0015] The angle of repose of the resin particles of the present invention is 20 to 65 degrees. When the angle of repose is within the above range, the powder is easily accumulated and a powder layer is easily formed, so that excellent slipperiness and a soft touch can be obtained when applied. The lower limit of the angle of repose is preferably 25 degrees, more preferably 30 degrees, even more preferably 33 degrees, and particularly preferably 35 degrees, and the upper limit of the angle of repose is preferably 63 degrees, more preferably 60 degrees, even more preferably 58 degrees, and particularly preferably 55 degrees. Furthermore, for example, 25 to 63 degrees is more preferable, 30 to 63 degrees is even more preferable, and 30 to 60 degrees is particularly preferable. The angle of repose of the resin particles is determined by the method described in the Examples.
[0016] The resin particles of the present invention are not particularly limited, but it is preferable that the value obtained by dividing the collapse angle by the above-mentioned repose angle (collapse angle / repose angle) is 0.5 to 1.0 in terms of obtaining a softer touch. The lower limit of the numerical value is more preferably 0.55, even more preferably 0.60, and particularly preferably 0.65, and the upper limit of the numerical value is more preferably 0.98, even more preferably 0.95, and particularly preferably 0.92. Furthermore, for example, 0.55 to 0.98 is more preferable, 0.60 to 0.98 is even more preferable, and 0.65 to 0.98 is particularly preferable. The collapse angle of the resin particles is measured by the method described in the Examples.
[0017] The sphericity of the resin particles of the present invention is not particularly limited, but is preferably 0.7 to 1.0. When the sphericity is 0.7 or more, the slipperiness tends to be improved. The sphericity is more preferably 0.8 to 1.0, further preferably 0.85 to 1.0, and particularly preferably 0.9 to 1.0. The sphericity of the resin particles can be calculated, for example, by image analysis, by dividing the minor axis of a particle photographed by a scanning electron microscope or the like by the major axis. In this case, when the ratio of the minor axis to the major axis is 1, the sphericity is 1.
[0018] The true specific gravity of the resin particles of the present invention is not particularly limited, but is preferably 0.8 to 1.8 g / cm. 3 The lower limit of the true specific gravity is preferably (1) 0.85 g / cm3 because of excellent slipperiness. 3 , (2) 0.90 g / cm 3 , (3) 0.93 g / cm 3 , (4) 0.95 g / cm 3 , (5) 0.98 g / cm 3 , (6) 1.0 g / cm 3 (The larger the value in parentheses, the more preferable it is.) On the other hand, the upper limit of the true specific gravity is (1) 1.7 g / cm 3 , (2) 1.6 g / cm 3 , (3) 1.55 g / cm 3 , (4) 1.5 g / cm 3 , (5) 1.45 g / cm 3 , (6) 1.4 g / cm 3(The larger the value in parentheses, the more preferable it is.) Furthermore, for example, 0.90 to 1.55 g / cm 3 More preferably, 1.0 to 1.4 g / cm 3 is more preferred.
[0019] The oleic acid oil absorption of the resin particles of the present invention is not particularly limited, but is preferably 30 to 150 mL / 100 g in terms of excellent slipperiness. The lower limit of the oil absorption is preferably (1) 35 mL / 100 g, (2) 40 mL / 100 g, (3) 45 mL / 100 g, and (4) 50 mL / 100 g in this order (the larger the value in parentheses, the more preferable). On the other hand, the upper limit of the oil absorption is preferably (1) 130 mL / 100 g, (2) 120 mL / 100 g, (3) 110 mL / 100 g, (4) 100 mL / 100 g, (5) 95 mL / 100 g, (6) 90 mL / 100 g, and (7) 85 mL / 100 g in this order (the larger the value in parentheses, the more preferable). For example, the oil absorption amount of the resin particles is more preferably 40 to 120 mL / 100 g, and further preferably 45 to 100 mL / 100 g. The oil absorption amount of the resin particles is measured by the method described in the Examples.
[0020] The water absorption of the polyester resin particles of the present invention is not particularly limited, but is preferably 20 to 150 mL / 100 g in terms of excellent slipperiness. The lower limit of the water absorption is preferably (1) 25 mL / 100 g, (2) 30 mL / 100 g, (3) 35 mL / 100 g, and (4) 40 mL / 100 g in this order (the larger the value in parentheses, the more preferable). On the other hand, the upper limit of the water absorption is preferably (1) 140 mL / 100 g, (2) 130 mL / 100 g, (3) 120 mL / 100 g, (4) 110 mL / 100 g, (5) 100 mL / 100 g, (6) 90 mL / 100 g, and (7) 85 mL / 100 g in this order (the larger the value in parentheses, the more preferable). For example, the water absorption amount of the particles is more preferably 30 to 120 mL / 100 g, and further preferably 40 to 100 mL / 100 g. The water absorption amount of the particles is determined by the method described in the Examples.
[0021] The resin particles of the present invention contain a polyester-based resin and are composed mainly of the polyester-based resin. The term "main component" refers to the component contained in the resin particles in the largest amount.
[0022] Examples of polyester resins include polycondensates of polyhydric alcohols and polycarboxylic acids, polycondensates of polyhydric alcohols, polycarboxylic acids and hydroxycarboxylic acids, polycondensates of hydroxycarboxylic acids, and polycondensates of derivatives thereof. Examples of polyester resins include aliphatic polyester resins, aromatic polyester resins, and aliphatic-aromatic polyester resins. Specifically, polylactic acid, polypropiolactone, polycaprolactone, polycaprolactone butylene succinate, polybutylene adipate caprolactone, polybutylene succinate hydroxycaproate, polybutylene succinate, polybutylene succinate adipate, polybutylene succinate carbonate, polybutylene succinate terephthalate, polybutylene succinate adipate terephthalate, polybutylene succinate lactate, polyethylene terephthalate, polytrimethylene terephthalate, polyethylene terephthalate copolymer, polybutylene adipate terephthalate, polytetramethylene adipate terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polybutylene adipate, polybutylene adipate terephthalate phthalate, polyethylene succinate, polyethylene adipate, polyethylene adipate terephthalate, polytetramethylene succinate, polypropylene succinate, polyhydroxyalkanoate, polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), polyhydroxybutyrate valerate, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), poly(3-hydroxybutyrate-co-3-hydroxypropionate), poly(3-hydroxybutyrate-co-4-hydroxybutyrate), poly(3-hydroxybutyrate-co-3-hydroxyacyl), polyhydroxyacyl, polyglycolic acid, lactic acid-glycolic acid copolymer, polyester elastomer, etc. may be used alone or in combination of two or more.
[0023] The polyester resin is not particularly limited, but if it contains at least one selected from an aliphatic polyester resin and an aliphatic-aromatic polyester resin, it is preferred in that resin particles having the specific melting enthalpy of the present invention are easily obtained, and the smoothness and soft touch are further improved, and furthermore, the resin can be biodegradable, which is preferable. As the aliphatic polyester resin, an aliphatic polyester resin containing an aliphatic polyhydric alcohol and an aliphatic polycarboxylic acid as constituent components, or an aliphatic polyester resin containing an aliphatic oxycarboxylic acid component as a constituent component is preferable. The aliphatic polyester resin is not particularly limited as long as the polyhydric alcohol, polycarboxylic acid, and hydroxycarboxylic acid, which are the components of the polyester resin, are aliphatic polyhydric alcohol, aliphatic polycarboxylic acid, and aliphatic hydroxycarboxylic acid, respectively.
[0024] Examples of the aliphatic polyhydric alcohols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, diethylene glycol, 1,5-pentanediol, 1,6-hexanediol, propylene glycol, dipropylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propanediol, 1,3-butanediol, 2,3-butanediol, neopentyl glycol (2,2-dimethylpropane-1,3-diol), 1,2-hexanediol, 2,5-hexanediol, 2-methyl-2,4-pentanediol, 3-methyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,2-bis(4-hydroxycyclohexyl)propane, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, trimethylolpropane, glycerin, and pentaerythritol. One or more of these may be used in combination.
[0025] Examples of the aliphatic polycarboxylic acid include succinic acid, adipic acid, suberic acid, sebacic acid, azelaic acid, octyl succinic acid, fumaric acid, maleic acid, itaconic acid, decamethylene dicarboxylic acid, and anhydrides thereof, and one or more of these may be used in combination. Examples of the aliphatic hydroxycarboxylic acid include lactic acid, glycolic acid, hydroxybutyric acid, hydroxycaproic acid, hydroxydimethylbutyric acid, and hydroxymethylbutyric acid, and one or more of these may be used in combination.
[0026] Examples of aliphatic polyester resins include polycaprolactone butylene succinate, polybutylene succinate, polybutylene succinate adipate, polybutylene succinate carbonate, polybutylene adipate, polybutylene succinate lactate, polyethylene succinate, polyethylene adipate, polytetramethylene succinate, polyhydroxyalkanoate, polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), polyhydroxybutyrate valerate, poly(3-hydroxybutyrate-co-3-hydroxyvalerate), poly(3-hydroxybutyrate-co-3-hydroxypropionate), poly(3-hydroxybutyrate-co-4-hydroxybutyrate), poly(3-hydroxybutyrate-co-3-hydroxyacyl), polyhydroxyacyl, and polylactic acid. These aliphatic polyester resins may be used alone or in combination of two or more.
[0027] The aliphatic-aromatic polyester resin is not particularly limited as long as the polyhydric alcohol, polycarboxylic acid, and hydroxycarboxylic acid, which are the components of the polyester resin, contain an aliphatic polyhydric alcohol, an aliphatic polycarboxylic acid, and an aliphatic hydroxycarboxylic acid, respectively, and further contain an aromatic polycarboxylic acid or a derivative thereof. Examples of aromatic polycarboxylic acids include o-phthalic acid, terephthalic acid, isophthalic acid, cyclohexanedicarboxylic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, trimellitic acid, and pyromellitic acid. The ratio of aromatic polycarboxylic acid-derived components in the aliphatic-aromatic polyester resin is preferably 40 unit mol% or less in terms of biodegradability. These aromatic polycarboxylic acids may be used alone or in combination of two or more.
[0028] Examples of the aliphatic-aromatic polyester resin include polybutylene succinate terephthalate, polybutylene adipate terephthalate, polytetramethylene adipate terephthalate, polybutylene succinate adipate terephthalate, etc. These aliphatic-aromatic polyester resins may be used alone or in combination of two or more.
[0029] The polyester resin is not particularly limited, but preferably has a weight average molecular weight of 5×10 3 ~1×10 9 The lower limit of the average molecular weight is preferably (1) 1 × 10 4 , (2) 2 × 10 4 , (3) 3 × 10 4 , (4) 5 × 10 4 , (5) 1 × 10 5 , (6) 2 × 10 5 , (7) 3 × 10 5 On the other hand, the upper limit of the average molecular weight is (1) 5 × 10 8 (2) 3 × 10 8 , (3) 1 × 10 8 , (4) 5 × 10 7 , (5) 3 × 10 7 , (6) 1 × 10 7 (The larger the number in parentheses, the more preferable it is.) Furthermore, for example, 2×10 4 ~5×10 8 is more preferable, and 3×10 4 ~5×10 8 is more preferred.
[0030] The weight ratio of the polyester resin in the resin particles of the present invention is not particularly limited, but is preferably 50 to 100% by weight. The lower limit of the weight ratio is preferably (1) 55% by weight, (2) 60% by weight, (3) 70% by weight, (4) 80% by weight, and (5) 90% by weight (the larger the value in parentheses, the more preferable). On the other hand, the upper limit of the weight ratio is preferably (1) 99.999% by weight, (2) 99.99% by weight, (3) 99.9% by weight, (4) 99% by weight, and (5) 98% by weight (the larger the value in parentheses, the more preferable). Furthermore, for example, 60 to 100% by weight is more preferable, 70 to 100% by weight is even more preferable, 80 to 100% by weight is particularly preferable, and 90 to 100% by weight is most preferable. In addition, it is preferable that the resin particles of the present invention are made of a polyester resin in terms of achieving the effects of the present application.
[0031] When the polyester resin contains at least one selected from aliphatic polyester resins and aliphatic-aromatic polyester resins, the weight ratio of the polyester resin in the polyester resin is not particularly limited, but is preferably 1 to 100% by weight. The lower limit of the weight ratio is preferably in the order of (1) 3% by weight, (2) 5% by weight, (3) 10% by weight, (4) 20% by weight, (5) 30% by weight, (6) 40% by weight, and (7) 50% by weight (the larger the value in parentheses, the more preferable it is). On the other hand, the upper limit of the weight ratio is more preferably 99.9% by weight, more preferably 99.5% by weight, and particularly preferably 99.0% by weight. Furthermore, for example, 5 to 100% by weight is more preferable, and 20 to 100% by weight is even more preferable. Furthermore, when the weight ratio of the aliphatic polyester resin in the polyester resin is 50% by weight or more, the soft touch tends to be improved and the material has biodegradability, which is particularly preferred.
[0032] The resin particles of the present invention may contain a resin other than the polyester-based resin (hereinafter, sometimes referred to as "other resin"). Examples of other resins include thermoplastic resins such as cellulose-based resins, polyvinyl-based resins, polyacrylic-based resins, polystyrene-based resins, polyolefin-based resins, polyether-based resins, polyamide-based resins, and thermoplastic polyurethane-based resins; and thermosetting resins such as silicone-based resins, phenol-based resins, unsaturated polyester-based resins, epoxy resins, melamine resins, and rubber. These resins may be used alone or in combination of two or more.
[0033] The resin particles of the present invention may contain, in addition to the polyester-based resin, at least one selected from a surfactant, an organic substance other than the above-mentioned resin, and an inorganic substance. Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, and silicone surfactants. Specific examples of the surfactant include anionic surfactants such as fatty acid salts, alkyl sulfate salts, alkyl ether carboxylate salts, alkyl ether sulfate salts, alkyl phosphate salts, polyoxyalkylene alkyl ether acetate salts, alkylbenzene sulfonate salts, polyoxyalkylene alkyl ether sulfate salts, higher fatty acid amide sulfonate salts, higher fatty acid alkali metal salts, alkyl phosphate salts, polyoxyalkylene alkyl ether phosphate salts, long-chain sulfosuccinate salts, and N-acylamino acid salts; cationic surfactants such as quaternary ammonium salts and alkylamine salts; polyoxyalkylene oxide-added alkyl ethers, and polyoxyalkylene styrenated phenyl. Examples of such surfactants include nonionic surfactants such as ethers, ester compounds of polyhydric alcohols and monovalent fatty acids, polyoxyalkylene alkylphenyl ethers, polyoxyalkylene fatty acid esters, polyoxyalkylene sorbitan fatty acid esters, glycerin fatty acid esters, PEG-hydrogenated castor oil, polyoxyalkylene castor oil, polyoxyalkylene hydrogenated castor oil, higher fatty acid PEG glyceryls, higher fatty acid sorbitans, polyoxyalkylene sorbitol fatty acid esters, polyglycerin fatty acid esters, alkyl glycerin ethers, polyoxyalkylene cholesteryl ethers, alkyl polyglucosides, sucrose fatty acid esters, and polysorbates; amphoteric surfactants such as amino acid-based, betaine-type, hydrogenated lecithin, and lecithin; and silicone-based surfactants such as modified dimethicone. These surfactants may be used alone or in combination of two or more.
[0034] Examples of organic substances include poorly water-soluble polysaccharides, water-soluble polymers, waxes, oils, fatty acids, fatty acid metal salts, amino acid compounds, etc., and these may be used alone or in combination of two or more kinds. The poorly water-soluble polysaccharide is not particularly limited as long as it has a solubility in water at 25° C. of 0.01 g / mL or less, and examples thereof include cellulose, chitin, chitosan, starch, and the like. The water-soluble polymer is not particularly limited as long as it has a solubility in water at 25°C of more than 0.01 g / mL, and examples thereof include sodium polyacrylate, polyvinylpyrrolidone, polyvinyl alcohol, polyalkylene oxides such as polyethylene oxide and polypropylene oxide, dextrin, sodium alginate, potassium alginate, mannan, xylan, xyloglucan, gum arabic, tamarind gum, pectin, pullulan, casein, xanthan gum, carrageenan, tragacanth gum, gelatin, hydroxyethyl cellulose, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, carboxyethyl cellulose, and the like.
[0035] Examples of the wax include higher alcohols, synthetic waxes, and paraffins. Examples of oils include almond oil, olive oil, rice bran oil, squalane, silicone oil, mineral oil, alkanes, and alkyl benzoates. Examples of fatty acids include lauric acid, myristic acid, palmitic acid, stearic acid, 12-hydroxystearic acid, behenic acid, montanic acid, and cerotic acid.
[0036] Examples of fatty acid metal salts include calcium laurate, zinc laurate, potassium laurate, zinc myristate, sodium myristate, zinc palmitate, sodium stearate, magnesium stearate, zinc stearate, calcium stearate, aluminum stearate, calcium 12-hydroxystearate, zinc 12-hydroxystearate, magnesium 12-hydroxystearate, aluminum 12-hydroxystearate, calcium behenate, zinc behenate, magnesium behenate, calcium montanate, zinc montanate, magnesium montanate, and aluminum montanate.
[0037] Examples of amino acid compounds include N-lauroyl-L-arginine, N-lauroyl-L-lysine, N-hexanoyl-L-lysine, N-oleyl-L-lysine, N-palmitoyl-L-lysine, N-stearinoyl-L-lysine, N-hexanoyl-L-lysine, N-myristenoyl-L-lysine, N-capryloyl-L-lysine, and N-decanoyl-L-lysine.
[0038] Examples of inorganic substances include wollastonite, sericite, kaolin, mica, clay, talc, bentonite, smectite, alumina silicate, pyrophyllite, montmorillonite, calcium silicate, calcium carbonate, magnesium carbonate, dolomite, calcium sulfate, boron nitride, silicon carbide, magnesium silicate, calcium silicate, magnesium aluminometasilicate, magnesium aluminometasilicate, hydroxyapatite, titanium oxide, silica, alumina, mica, titanium dioxide, zinc oxide, magnesium oxide, zinc oxide, hydrosaltite, and boron nitride.
[0039] The resin particles of the present invention are not particularly limited, but further contain at least one selected from a surfactant and a water-soluble polymer, and when the total weight ratio of the surfactant and the water-soluble polymer in the resin particles is 0.001 to 10% by weight, it is preferable in that the resin particles having the specific performance of the present invention are easily obtained and the soft touch is improved. The lower limit of the total amount is preferably (1) 0.002% by weight, (2) 0.005% by weight, (3) 0.01% by weight, (4) 0.02% by weight, (5) 0.05% by weight, and (6) 0.1% by weight (the larger the value in parentheses, the more preferable). On the other hand, the upper limit of the weight ratio is preferably (1) 8% by weight, (2) 6% by weight, (3) 5% by weight, (4) 4% by weight, and (5) 3% by weight (the larger the value in parentheses, the more preferable). Furthermore, for example, 0.001 to 8% by weight is more preferable, and 0.001 to 5% by weight is even more preferable.
[0040] Although there is no particular limitation, the resin particles of the present invention preferably have a biodegradability of 1% or more after 10 days as measured in accordance with JIS K6950: 2000. The lower limit of the biodegradability is preferably (1) 3%, (2) 5%, (3) 10%, (4) 15%, (5) 20%, (6) 25%, and (7) 30% in that order (the larger the number in parentheses, the more preferable it is).
[0041] The resin particles of the present invention can be produced, for example, by a method including the following steps 1 to 3 (hereinafter sometimes referred to as a particle production method). Step 1: Mix a polyester resin, a surfactant, a water-soluble polymer, and water to obtain a preliminary mixture. Step 2: Heat and stir the preliminary mixture obtained in step 1 to obtain a heated dispersion. Step 3: Cooling the heated dispersion obtained in step 2
[0042] The resin particles of the present invention are preferable in that the particles having excellent slipperiness and soft touch can be suitably produced when the resin particles are produced without using an organic solvent. It is presumed that by producing the particles using water without using an organic solvent, the surfactant and the water-soluble polymer are easily present at the interface between the particles and the water during particle formation, which contributes to improving the surface properties of the particles. Furthermore, it is presumed that the polarity of the particle surface is appropriately maintained during particle formation by not using an organic solvent, and the particles have a specific particle size and angle of repose, resulting in particles having excellent slipperiness and a soft touch. It is also considered that the lipophilic group of the surfactant affects the resin structure, resulting in a specific enthalpy of fusion, and resin particles having excellent slipperiness and a soft touch can be obtained. In addition, not using an organic solvent is environmentally friendly and preferable.
[0043] The surfactant is not particularly limited, but the surfactants described above can be used. The surfactant to be used is preferably at least one selected from an anionic surfactant and a nonionic surfactant, and more preferably a nonionic surfactant, since this makes it possible to make the shape of the resin particles more uniform and makes it easier to obtain particles having a specific angle of repose. The anionic surfactant is not particularly limited, but it is preferable to use at least one selected from sulfate ester salts and sulfonate salts, and it is more preferable to use sulfonate salts. The nonionic surfactant is not particularly limited, but it is preferable to use an ester compound of a polyhydric alcohol and a monovalent fatty acid, and it is more preferable to use at least one selected from glycerin fatty acid esters and higher fatty acid sorbitans. The surfactant is not particularly limited, but it is preferable to use a nonionic surfactant with an HLB value of 1 to 13, since this tends to have a specific melting enthalpy. The HLB value is more preferably 1 to 11, further preferably 1 to 10, and particularly preferably 1.5 to 10. The HLB value can be calculated, for example, from the following Griffin method formula (1). HLB = 20 × (molecular weight of hydrophilic group / total molecular weight) (1) Furthermore, it is preferable to use an ester type or ester salt type surfactant, since this makes it easier to obtain resin particles having a specific particle size and angle of repose, and provides an excellent soft feel.
[0044] The surfactant may be finally contained in the resin particles. The presence of the surfactant near the particle surface is considered to have a greater effect on the surface structure, making it easier to obtain particles having a specific angle of repose. The weight ratio of the surfactant in the resin particles is not particularly limited, but is preferably 0.001 to 10% by weight, and the upper limit of the weight ratio is more preferably 7% by weight, and even more preferably 5% by weight. On the other hand, the lower limit of the weight ratio is more preferably 0.005% by weight, and even more preferably 0.01% by weight. Furthermore, for example, it is more preferably 0.001 to 7% by weight, and even more preferably 0.001 to 5% by weight.
[0045] The water-soluble polymer can be any of those mentioned above, and is preferably a water-soluble polymer whose viscosity of a 4% aqueous solution at 20°C is 2 to 200,000 mPa·s, in that it is easy to obtain resin particles having a specific particle size. The water-soluble polymer is preferably at least one selected from polyvinylpyrrolidone, polyvinyl alcohol, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, and carboxymethyl cellulose, and more preferably polyvinyl alcohol, in that resin particles having a specific particle size can be easily obtained and the slipperiness can be further improved.
[0046] The water-soluble polymer may be finally contained in the resin particles. It is considered that the presence of the water-soluble polymer in the resin particles leads to better slip properties. The weight ratio of the water-soluble polymer in the resin particles is not particularly limited, but is preferably 0.001 to 10% by weight, and the upper limit of the weight ratio is more preferably 8% by weight, and even more preferably 5% by weight. On the other hand, the lower limit of the weight ratio is more preferably 0.002% by weight, and even more preferably 0.005% by weight. Furthermore, for example, it is more preferably 0.001 to 8% by weight, and even more preferably 0.001 to 5% by weight.
[0047] (Process 1) Step 1 is a step of mixing a polyester resin, a surfactant, a water-soluble polymer, and water to obtain a preliminary mixed liquid. When the resin particles contain components other than the polyester resin, the surfactant, and the water-soluble polymer, it is preferable to add and mix the other components in this step.
[0048] In step 1, the mixing ratio of the polyester resin is not particularly limited, but is preferably 1 to 200 parts by weight per 100 parts by weight of water. When the mixing ratio is within the above range, it is preferable because resin particles having a more uniform shape and a specific particle size are easily obtained. The lower limit of the mixing ratio is more preferably 3 parts by weight, even more preferably 5 parts by weight, and most preferably 10 parts by weight. On the other hand, the upper limit of the mixing ratio is more preferably 180 parts by weight, even more preferably 160 parts by weight, and most preferably 150 parts by weight. Furthermore, for example, 5 to 200 parts by weight is more preferable, and 10 to 180 parts by weight is even more preferable.
[0049] In step 1, the mixing ratio of the surfactant is not particularly limited, but is preferably 0.001 to 10 parts by weight relative to 100 parts by weight of the polyester resin. When the mixing ratio is within the above range, the resin particles having the specific performance of the present invention are easily obtained, and the obtained resin particles tend to have improved slipperiness and soft touch, which is preferable. The lower limit of the mixing ratio is preferably 0.01 parts by weight, more preferably 0.05 parts by weight, and particularly preferably 0.1 parts by weight. The upper limit of the mixing ratio is more preferably 7 parts by weight, even more preferably 5 parts by weight, and particularly preferably 3 parts by weight. Furthermore, for example, 0.001 to 7 parts by weight is more preferable, and 0.01 to 7 parts by weight is even more preferable.
[0050] In step 1, the mixing ratio of the water-soluble polymer to water is not particularly limited, but is preferably 0.1 to 100 parts by weight per 100 parts by weight of water. When the mixing ratio is within the above range, resin particles having a specific particle size are easily obtained, and the dispersibility of the obtained polyester resin particles tends to be improved. The lower limit of the ratio is more preferably 0.5 parts by weight, even more preferably 1 part by weight, and particularly preferably 2 parts by weight. On the other hand, the upper limit of the ratio is more preferably 80 parts by weight, even more preferably 70 parts by weight, and particularly preferably 60 parts by weight. Furthermore, for example, 0.5 to 100 parts by weight is more preferable, and 1 to 100 parts by weight is even more preferable.
[0051] When the resin particles of the present invention are produced by mixing a surfactant and a water-soluble polymer, the viscosity of the liquid during production is improved by the water-soluble polymer, and the efficiency of particle uniformization is improved by the surfactant, which is considered to contribute to uniform particle size distribution and surface properties of the particles, and it is easy to obtain resin particles having a specific particle size and angle of repose, and it is further preferable in that resin particles having excellent slip properties and a soft touch can be obtained. In order to further improve the slip properties and soft touch, it is further preferable that the weight ratios of the surfactant and the water-soluble polymer are within the above-mentioned ranges.
[0052] (Process 2) Step 2 is a step of heating and stirring the preliminary mixture obtained in step 1 to obtain a heated dispersion. The pressure during heating and stirring in step 2 is not particularly limited, but is preferably 0.1 to 10 MPa. If the pressure is within the above range, resin particles having a specific particle size tend to be obtained, which is preferable. The pressure is preferably equal to or higher than the saturated vapor pressure of water at the heating temperature. The heating temperature is not particularly limited, but is preferably 80 to 300°C. When the temperature is within the above range, resin particles having the specific performance of the present invention are easily obtained, and the shape of the obtained resin particles tends to be more uniform, which is preferable. The temperature is preferably a temperature equal to or higher than the softening point or melting point of the polyester resin, more preferably a temperature 5°C or higher than the softening point or melting point of the polyester resin, even more preferably a temperature 10°C or higher, and particularly preferably a temperature 15°C or higher. By heating to a temperature equal to or higher than the softening point or melting point, the lipophilic group of the surfactant acts on the polyester resin and easily affects the resin structure, and the surfactant and the water-soluble polymer are uniformly present at the interface between the polyester resin and water, which is preferable because it is easy to obtain resin particles having a specific particle size, angle of repose, and specific enthalpy of fusion. In step 2, it is preferable to heat the mixture to a temperature equal to or higher than the softening point or melting point of the polyester resin and stir the mixture under a pressure of 0.1 MPa or more, since this makes it easier to obtain resin particles having a specific particle size and fusion enthalpy.
[0053] The stirring method is not particularly limited, and it is sufficient that the mixture is stirred to a degree that allows it to be mixed. The heating time is not particularly limited, but is preferably 1 to 30 hours. When the time is 1 hour or more, resin particles are more uniformly dispersed and have a specific particle size and fusion enthalpy, which is preferable. When the time is 30 hours or less, production efficiency tends to improve. The lower limit of the time is more preferably 2 hours, even more preferably 3 hours, and most preferably 5 hours. The upper limit of the heating time is more preferably 25 hours, even more preferably 20 hours, and most preferably 15 hours. Furthermore, for example, 3 to 20 hours is more preferable, and 3 to 15 hours is even more preferable.
[0054] (Step 3) Step 3 is a step of cooling the heated dispersion obtained in step 2. By cooling the heated dispersion in step 2, a dispersion of resin particles can be obtained. The cooling method is not particularly limited, but it is preferable to cool the heated dispersion obtained in step 2 to 5 to 50° C. The cooling rate is not particularly limited, but it may be rapid cooling or natural cooling by air cooling or the like. In step 3, stirring may be continued at the stirring speed in step 2, or stirring may be stopped. The dispersion after cooling is an aqueous dispersion containing resin particles.
[0055] The resin particles of the present invention may be used in the form of a dispersion, a wet powder, or a dry powder. The wet powder can be obtained by dehydrating the dispersion in step 3 using, for example, a centrifuge, a pressure press, a vacuum dehydrator, or the like. The dispersion in step 3 may be dehydrated after a measure to reduce the liquid viscosity is taken. The method for reducing the liquid viscosity is not particularly limited, but examples thereof include a method of diluting the liquid by adding water, a method of salting out water-soluble components, and a method of decomposing water-soluble components with an oxidizing agent or enzymes.
[0056] The dry powder can be obtained by drying the wet powder using a tray dryer, an indirect heating dryer, a fluidized bed dryer, a vacuum dryer, a vibration dryer, an airflow dryer, etc. Alternatively, the dispersion obtained in step 3 can be dried using a spray dryer, a fluidized bed dryer, etc. to obtain a dry powder. The dried powder may be classified by air classification, screen classification, or the like.
[0057] [Uses of polyester resin particles] The resin particles of the present invention can be used in cosmetics, paints, optical applications, resins, building materials, etc. In particular, the resin particles of the present invention are excellent in slipperiness and can be suitably used in cosmetics and coating compositions. In addition, since they have a soft feel, they can provide a comfortable feel when blended into cosmetics.
[0058] When used in cosmetics, it can be used in combination with known cosmetic ingredients. Examples of cosmetic ingredients include oils, surfactants, alcohols, water, moisturizers, gelling agents, thickeners, powders other than the polymer particles of the present invention, UV absorbers, preservatives, antibacterial agents, antioxidants, functional ingredients, etc. Examples of the form of the cosmetic containing the polymer particles of the present invention include powder, solid, cream, gel, liquid, mousse, spray, etc. The weight ratio of the polymer particles to the entire cosmetic is not particularly limited, but is preferably 0.1 to 50% by weight, more preferably 0.5 to 30% by weight, and even more preferably 1 to 20% by weight.
[0059] When used in a coating composition, it can be used in combination with known coating components. The weight proportion of the polymer particles in the entire coating composition is not particularly limited, but is preferably 0.1 to 30% by weight, more preferably 0.5 to 20% by weight, and further preferably 1 to 10% by weight. EXAMPLES
[0060] Examples of the polyester-based resin particles of the present invention will be specifically described below. Note that the present invention is not limited to these examples. In addition, the resin particles shown in the examples and comparative examples were measured for physical properties and further evaluated in the following manner.
[0061] (Measurement of particle size (D10), particle size (D50), particle size (D90) of polyester resin particles) Measurements were performed using a laser diffraction scattering type particle size distribution measuring device (Microtrac particle size distribution meter (model 9320-HRA), manufactured by Nikkiso Co., Ltd.) by irradiating ultrasonic waves for 120 seconds using the wet measurement method. The volume-based cumulative particle diameter means the diameter of particles relative to a predetermined ratio of the cumulative distribution obtained by integrating all particles in order from the smallest volume.
[0062] In principle, laser diffraction scattering particle size analyzers measure the distribution of cumulative particle sizes based on volume, and the measurement values of the cumulative 10% particle size (D10), cumulative 50% particle size based on volume (D50), and cumulative 90% particle size based on volume (D90) can be confirmed using the measuring device's software.
[0063] (Measurement of Melting Enthalpy and Maximum Melting Peak Temperature of Polyester Resin Particles) A differential scanning calorimeter (Jada DSC LAB SYSTEC, manufactured by ParkinElmer) was used as the measuring device, and the temperature was raised from 30° C. to 250° C. at 10° C. / min in a nitrogen atmosphere to calculate the melting peak temperature and melting enthalpy. The endothermic peak top temperature was taken as the melting peak temperature, and when multiple endothermic peaks existed, the temperature at which the largest endothermic peak was reached was taken as the maximum melting peak temperature of the resin particles. The melting enthalpy of the resin particles was determined as the sum of the enthalpies of all endothermic peaks.
[0064] (Measurement of angle of repose and angle of collapse of polyester resin particles) The measurement was performed using a multi-function powder property measuring instrument (MULTITESTER MT-1001, manufactured by Seishin Enterprise Co., Ltd.) at room temperature of 25° C. and humidity of 40%.
[0065] (Measurement of Sphericity of Polyester Resin Particles) Particles were observed at 1000x magnification using a scanning electron microscope, and the short and long diameters of 30 randomly selected particles were measured. The short diameter was divided by the long diameter for each particle to calculate the value, and the average of the calculated values for the 30 particles was taken as the sphericity. For example, when the ratio of the short diameter to the long diameter is 1, the sphericity is 1.
[0066] (Measurement of water absorption and oil absorption of polyester resin particles) Based on the JIS-K5101 oil absorption measurement method, the water absorption was measured using ion-exchanged water and the oil absorption was measured using oleic acid.
[0067] (Particle Evaluation) 0.05 g of the particles were weighed out and placed on the edge of a 10 cm x 5 cm piece of black artificial leather (product name: Suppurare, manufactured by Ideatech Japan), and spread in one direction with a finger. The smoothness and softness of the particles were evaluated according to the following criteria. <Slipperiness> ◎: Can be applied smoothly. ◯: Slightly adhesive, but can be applied smoothly. △: Strong adhesion, poor slipperiness. ×: Cannot be applied. <Soft feel> ◎: Feels soft when applied. ◯: Feels slightly soft when applied. △: Feels a little hard when applied. ×: Feels hard when applied.
[0068] Example 1 300 parts by weight of water, 100 parts by weight of polybutylene succinate, 1 part by weight of sorbitan monolaurate (HLB value: 8.6), and 20 parts by weight of polyvinyl alcohol were mixed and charged into a 1 L pressure vessel, which was then sealed. The temperature inside the vessel was raised to 140°C, and the mixture was stirred at 400 rpm per minute under a pressure of 0.5 MPa for 3 hours, and then cooled to 50°C to obtain an aqueous dispersion of resin particles. An oxidizing agent was added to the aqueous dispersion, which was then dehydrated by filtration, dried at 50°C, and classified to obtain particles 1. The weight percentage of the surfactant in particles 1 was 0.5% by weight, and the weight percentage of polyvinyl alcohol was 0.3% by weight. The physical properties of the obtained particles 1 are shown in Table 1.
[0069] Example 2 300 parts by weight of water, 80 parts by weight of polyhydroxyalkanoate, 20 parts by weight of polybutylene succinate, 3 parts by weight of sorbitan monolaurate (HLB value: 8.6), and 20 parts by weight of polyvinyl alcohol were mixed and charged into a 1 L pressure vessel and sealed. The temperature inside the vessel was raised to 160°C, and the mixture was stirred at 400 rpm per minute for 10 hours under a pressure of 1.0 MPa, and then cooled to 50°C to obtain an aqueous dispersion of resin particles. An oxidizing agent was added to the aqueous dispersion, and the mixture was washed with a large amount of water, dehydrated by filtration, dried at 50°C, and classified to obtain particles 2. The weight percentage of the surfactant in particles 2 was 0.8% by weight, and the weight percentage of polyvinyl alcohol was 0% by weight. The physical properties of the obtained particles 2 are shown in Table 1.
[0070] Example 3 300 parts by weight of water, 100 parts by weight of polybutylene succinate adipate, 1 part by weight of sorbitan monostearate (HLB value: 4.7), 1 part by weight of fumed silica, and 20 parts by weight of polyvinyl alcohol were mixed and charged into a 1 L pressure vessel and sealed. The temperature inside the vessel was raised to 120°C, and the mixture was stirred at 400 rpm per minute under a pressure of 0.5 MPa for 3 hours, and then cooled to 50°C to obtain an aqueous dispersion of resin particles. An oxidizing agent was added to the aqueous dispersion, which was then dehydrated by filtration, dried at 50°C, and classified to obtain particles 3. The weight ratio of the surfactant in particles 3 was 0.7% by weight, and the weight ratio of polyvinyl alcohol was 2.0% by weight. The physical properties of the obtained particles 3 are shown in Table 1.
[0071] Example 4 200 parts by weight of water, 50 parts by weight of polybutylene succinate, 50 parts by weight of polybutylene succinate adipate, 0.1 parts by weight of sorbitan monolaurate (HLB value: 8.6), 0.5 parts by weight of diethylhexyl sodium sulfosuccinate, and 30 parts by weight of polyvinyl alcohol were mixed and charged into a 1 L pressure vessel and sealed. The temperature inside the vessel was raised to 140°C, and the mixture was stirred at 200 rpm per minute under a pressure of 1.0 MPa for 5 hours, and then cooled to 50°C to obtain an aqueous dispersion of resin particles. The aqueous dispersion was washed with a large amount of water, dehydrated by filtration, dried at 50°C, and classified to obtain particles 4. The weight percentage of the surfactant in particles 4 was 0% by weight, and the weight percentage of polyvinyl alcohol was 0.01% by weight. The physical properties of the obtained particles 4 are shown in Table 1.
[0072] Example 5 300 parts by weight of water, 100 parts by weight of polybutylene adipate terephthalate, 2 parts by weight of sorbitan sesquioleate (HLB value: 3.7), and 30 parts by weight of polyvinyl alcohol were mixed and charged into a 1 L pressure vessel and sealed. The temperature inside the vessel was raised to 140°C, and the mixture was stirred at 400 rpm per minute under a pressure of 1.0 MPa for 5 hours, and then cooled to 50°C to obtain an aqueous dispersion of resin particles. The aqueous dispersion was washed with a large amount of water, dehydrated by filtration, dried at 50°C, and classified to obtain particles 5. The weight percentage of the surfactant in particles 5 was 0% by weight, and the weight percentage of polyvinyl alcohol was 0%. The physical properties of the obtained particles 5 are shown in Table 1.
[0073] Comparative Example 1 Polylactic acid particles (product name: ECOBEADS D-5, manufactured by Daito Kasei Kogyo Co., Ltd.) were similarly measured and evaluated. The physical properties are shown in Table 1.
[0074] Comparative Example 2 20 parts by weight of water, 10 parts by weight of polybutylene succinate, 30 parts by weight of 3-methoxy-3-methyl-1-butanol, 35 parts by weight of a 10% aqueous solution of calcium phosphate tribasic, and 0.04 parts by weight of sodium lauryl sulfate were mixed and charged into a 1L pressure-resistant container and sealed. The temperature inside the container was raised to 120°C, and the mixture was stirred at 400 rpm per minute at a pressure of 0.5 MPa for 1 hour, and then cooled to 30°C to obtain a particle dispersion. 14 parts by weight of 20% hydrochloric acid was added to the dispersion, and after stirring for 20 minutes, the mixture was dehydrated by filtration, washed with a large amount of water, dried at 50°C, and classified to obtain particles. The evaluation results of the obtained particles are shown in Table 1.
[0075] [Table 1]
[0076] The resin particles of Examples 1 to 5 had excellent slipperiness and a soft feel. In addition, it was confirmed that the resin particles had excellent slipperiness and applicability and a soft feel when used for artificial leather, which is a soft material with a feel similar to human skin. On the other hand, the particles of Comparative Examples 1 and 2 had a melting enthalpy outside the range, felt hard, and had poor lubricity. [Industrial Applicability]
[0077] The resin particles of the present invention have excellent slip properties and a soft feel, and are therefore useful as an additive for cosmetics and coating agents.
Claims
1. Contains polyester resin, A volume-based cumulative 50% particle size (D50) is 1 to 100 μm, a fusion enthalpy is 20 to 140 J / g, and a repose angle is 20 to 65 degrees, The water absorption capacity is 20 to 130 mL / 100 g, and it is used as an ingredient in cosmetics. Polyester resin particles.
2. 2. The polyester resin particles according to claim 1, wherein the maximum melting peak temperature is from 50 to 250° C.
3. 3. The polyester resin particles according to claim 1, wherein the oleic acid oil absorption is from 30 to 150 mL / 100 g.
4. 3. The polyester-based resin particles according to claim 1, wherein the polyester-based resin comprises at least one selected from the group consisting of an aliphatic polyester-based resin and an aliphatic-aromatic polyester-based resin.
5. A polyester-based resin particle as described in claim 1 or 2, comprising at least one selected from a water-soluble polymer and a surfactant, and the weight proportion of the polyester-based resin in the polyester-based resin particle is 50 to 99.999 weight %.
6. A cosmetic comprising the polyester-based resin particles according to claim 1 or 2.
Citation Information
Patent Citations
Resin powder for solid molding and manufacturing machine of solid molding
JP2018154116A
Cosmetic composition containing biodegradable resin particle
JP2019210256A
Resin particles and method for producing the same
JP2022161001A
Water dispersion of polybutylene succinate adipate resin particle, method for producing the same, and polybutylene succinate adipate resin particle
JP2023144303A
JPP7377924B